Effects of Chrysin on Oral Squamous Cell Carcinoma In Vitro - Puengsurin, Duangchewan; Buranapraditkun, Supranee; Leewansangtong, Chayanee; Taechaaukarakul, Nitchakarn; Songsivilai, Proud; Surarit, Rudee; Kitkumthorn, Nakarin (European Journal of Dentistry, 2022)
Objective Chrysin is a hydroxylated flavonoid derived from “propolis or bee glue,” a natural product. Previous research on chrysin's biological functions, including anticancer activity, had been reported. However, chrysin's effect on oral squamous cell carcinoma (OSCC) is still scarce. This article aimed to test the cytotoxicity, antiproliferative, antimigration, anti-invasion, and apoptotic effects of purified chrysin in two OSCC cell lines, HSC4 and SCC25.Materials and Methods The malignant phenotype was assessed using cell proliferation, wound healing, and transwell assays. Cell apoptosis was determined using flow cytometry. The positive control was OSCC cells treated with cisplatin, and the negative control was OSCC cells incubated with 0.1% dimethyl sulfoxide.Results Chrysin at concentrations of 100 and 200 µM could inhibit OSCC cell proliferation, migration, and invasion, as well as enhance cell apoptosis, particularly in the early stages of apoptosis.Conclusion In OSCC cell lines, chrysin has been demonstrated to be an effective antioncogenic agent. Additional research is required to confirm the results. Chrysin should be suggested as a possible alternative therapeutic application for OSCC.
Keywords: chrysin; oral squamous cell carcinoma; proliferation; migration; invasion; apoptosis